Violência sexual doméstica contra crianças e adolescentes: um estudo sobre o município de Foz do Iguaçu-Pr - Ziglioli, Claires Salete (2016)
This Master's Dissertation study aimed to analyze the domestic sexual violence against children and adolescents: a study of the city of Foz do Iguaçu-Pr, city of the Triple Frontier of Brazil, Argentina and Paraguay. The procedure began with the approach of the phenomenon of violence in its forms of structural violence and domestic violence. Subsequently, reference was made to the Integral Protection System, highlighting the Law Guarantee System, represented by Service Network in combating sexual violence, as well as the Combat Plans Sexual Violence against Children and National Teenagers, State and Municipal. The research took place in the SINAN, and in the organs (Guardianship Councils I and II, CREAS, NUCRIA, MP, Shelter and IML) identified as full protection in Foz do Iguaçu. It tried, thus, understand the coping flow to sexual violence against children and adolescents, as well as compliance with the actions of the Municipal Plan to Combat Sexual Violence against Children and Adolescents in the city. The methodology privileged the qualitative-quantitative approach, enriched with information obtained through the questionnaire and survey data online and on-site, next to the sectors in the year 2014. The data analysis was performed with a qualitative reading in the light of the theoretical framework, key to highlight some categories such as online data type of sexual violence; consequences of violence; author data aggression; referrals to the sectors that make up the organizational and functional structure of children and adolescents rights guarantee system; research on the spot, next to the Guardianship Councils I and II, the CREAS, the NUCRIA, the prosecutor, the Shelter and the IML, to map the number of cases received, accompanied and directed by them to other sectors; yet the actions undertaken by sectors, in relation to compliance with the structural axes of the Municipal Plan to Combat Sexual Violence against Children and Adolescents. According to the survey results, it was concluded that the flow of service and the Municipal Plan does not advocate in the city of Foz do Iguaçu in fighting domestic sexual violence against children and adolescents. Still, regarding the relationship between the Municipal Plan to Combat Sexual Violence against Children and Adolescents and the flow of care to sexual violence, it was found that children and adolescents remain being raped not only within the family, but by the institucions that should ensure their full protection.